Participatory Action for Optimizing Health Literacy and Access to Manage Hypertension: Pre-post Evaluation in a Marginalized Community of India - Reetu Passi; Manmeet Kaur; Madhu Gupta; Savita Kumari; Rajesh Kumar (SAGE Open)
We used a participatory action research (PAR) strategy for optimizing health literacy and access (Ophelia) to improve hypertension (HTN) management in a peri-urban village of Chandigarh (India). We used an embedded mixed method design for development, implementation, and evaluation. Through community consultations and vignettes created from interviews with population sub-groups and input from healthcare providers, we co-designed the intervention. Volunteers facilitated community-based awareness activities like door-to-door interaction, mobile messages, posters, collaboration with healthcare providers, and free blood pressure monitoring services. At the health facility, we improved communication by re-orienting healthcare providers and introducing medication adherence charts after identifying gaps through patients’ journeys. We measured changes in health literacy, HTN knowledge, risk factors, medication adherence, and HTN control in a sample of 510 randomly selected adults in pre and post-intervention design using chi-square and t -test. A checklist assessed community capacity and multivariable regression adjusted the effect of confounders. Health literacy significantly improved across most scales (beta range 0.17 to 0.76, p  < 0.01). Hypertension knowledge scores increased from 2.9 to 3.4 ( p  < 0.05). Physical activity (≥1,500 MET min/week) (aOR 0.19, 95% CI 0.11 to 0.33, p  < 0.01) and daily salt consumption (<5 g/day) (aOR 0.47, 95% CI 0.36 to 0.6, p  < 0.01) improved. However, body weight, tobacco and alcohol use remained unchanged. Medication adherence (aOR 0.08; 95% CI 0.02 to 0.32 p < 0.01) and HTN control (aOR 0.28; 95% CI 0.08 to 0.94; p  = −0.04) increased. Community capacity in leadership, planning, management, learning and skill development received high rating.